PJMHS 2023
DOI: 10.53350/pjmhs2023173697
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression among Patients with Type-1 and Type-2 Diabetes Mellitus

Abstract: The diabetic patients are more likely to experience depression. The study's objective was to determine the depression prevalence in newly diagnosed patients with type-I (T1DM) and type-II (T2DM) diabetes, as well as the relationship between these symptoms and several independent clinical and sociodemographic variables. Place and Duration: Study took place in the Department of Endocrinology and metabolism in Services Hospital Lahore, Pakistan for six months of duration from January 2017 to June 2017. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…This relationship was consistent across both Type 1 and Type 2 diabetes subgroups. This is also in affirmation with the study that found both individual with type 1 and type 2 diabetes have significantly higher depression respectively 27 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This relationship was consistent across both Type 1 and Type 2 diabetes subgroups. This is also in affirmation with the study that found both individual with type 1 and type 2 diabetes have significantly higher depression respectively 27 .…”
Section: Discussionsupporting
confidence: 84%
“…Diabetes distress, related to the emotional burden of managing the condition, correlates strongly with depression, affecting patient well-being and adherence to treatment 20 – 25 . This distress, found in 36% of those with Type 2 diabetes, is notably higher in those with depressive symptoms 26 , 27 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation